2010
DOI: 10.1074/jbc.m109.094524
|View full text |Cite
|
Sign up to set email alerts
|

A Pathway Involving Farnesoid X Receptor and Small Heterodimer Partner Positively Regulates Hepatic Sirtuin 1 Levels via MicroRNA-34a Inhibition

Abstract: Sirtuin 1 (SIRT1) is a NAD-dependent deacetylase that is critically involved in diverse cellular processes including metabolic disease, cancer, and possibly aging. Despite extensive studies on SIRT1 function, how SIRT1 levels are regulated remains relatively unknown. Here, we report that the nuclear bile acid receptor farnesoid X receptor (FXR) inhibits microRNA-34a (miR34a) in the liver, which results in a positive regulation of SIRT1 levels. Activation of FXR by the synthetic agonist GW4064 decreases hepatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
201
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 233 publications
(224 citation statements)
references
References 40 publications
15
201
0
Order By: Relevance
“…3A). Similar feedback loops have been described for a number of miRNAs in a host of different biological systems (4,16,29,30,32,34,45,46,48,52,57) and recently was described for miR-24 and menin in the parathyroid (32). miR-24 is produced from two separate chromosomal locations in both the human and mouse genomes (Fig.…”
Section: Mir-24 Impacts Cell Viability and Proliferation In Vitromentioning
confidence: 96%
“…3A). Similar feedback loops have been described for a number of miRNAs in a host of different biological systems (4,16,29,30,32,34,45,46,48,52,57) and recently was described for miR-24 and menin in the parathyroid (32). miR-24 is produced from two separate chromosomal locations in both the human and mouse genomes (Fig.…”
Section: Mir-24 Impacts Cell Viability and Proliferation In Vitromentioning
confidence: 96%
“…Consistent with their critical biological functions, miRs are aberrantly expressed in human diseases, such as metabolic disease and cancer (10,12). We have shown that miR-34a, which targets SIRT1 deacetylase, is aberrantly elevated in fatty livers of high-fat (HF) diet-induced obese mice and leptin-deficient ob/ob mice and that miR-34a is the most highly elevated hepatic miR in metabolic disease-prone FXR-null mice (13,14). Consistent with these findings, a recent study has shown that miR34a was the most highly elevated hepatic miR in dietary and genetic obese mice (15).…”
mentioning
confidence: 87%
“…S1). Down-regulation of miR-34a by antisense miR-34a in mouse Hepa1c1c7 cells resulted in a dose-dependent increase in expression of βKL, as well as a known miR-34a target, SIRT1 (14,20) (Fig. 1 A-D and SI Appendix, Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…miR-103/ 107 and let-7 mainly regulate insulin signalling in peripheral tissues such as adipose tissue and skeletal muscle by targeting caveolin-1 and IR/IRS2, respectively 15,16 . miR-143 and miR-34a affect hepatic insulin signalling by targeting oxysterol-bindingprotein-related protein 8 (ORP8) and Sirtuin 1 (SIRT1), respectively 17,18 . miR-33 affects hepatic insulin action by targeting multiple metabolic regulators, including Sirtuin 6 (SIRT6), a1 subunit of AMP-activated protein kinase (AMPKa1) and IRS2.…”
mentioning
confidence: 99%